Congenital nephrotic syndrome and renal vein thrombosis in infancy. Issue 1 (February 1971) - Alexander, F.; Campbell, W. A. B.
Abstract : Three of the four cases of the nephrotic syndrome in infancy described show the typical clinical and pathological features of the commonly termed congenital nephrotic syndrome, and two of them abnormal immunoglobulins. Two of the infants were siblings. The placental abnormalities and renal electron microscopic changes are reported and are believed to be involved in antigen-antibody reactions. The literature is reviewed and the possible aetiology of these lesions is discussed. The fourth case is considered to be due to thrombosis of the inferior vena cava and renal veins, an extremely rare cause of the nephrotic syndrome in infants.